How to Reduce the Risk of Colliding Change Initiatives - Huy, Quy; Huy, Quy; Kanitz, Rouven; Backmann, Julia; Hoegl, Martin (MIT Sloan Management Review, 2021)
Where should leaders focus when managing multiple, simultaneous change initiatives? Recent research by the authors explores the experiences of a global technology company that attempted two concurrent large-scale change initiatives. In this scenario, consistency around content, procedure, and normative expectations as perceived by employees stood out as the pivotal success factor.